Das sufragistas às ativistas 2.0: feminismo, mídia e política no Brasil (1921 a 2016) - Rayza Sarmento de Sousa (2017)
This thesis discusses the relationship between feminism, politics and the media in Brazil in order to understand the discursive construction of the movement in the media and the ways in which feminist activists interact with these public discourses. Our theoretical contribution comes from two paths: feminist political theory and feminists media studies. We review how gender studies have addressed central issues of political thinking and the democratic canon, arguing that the debates about subject and public versus private are central to understanding the hierarchies of gender arranged in different spheres of political life. These notions were used as categories of empirical material analysis. Empirically, we conducted qualitative frame analysis of news in the Folha de São Paulo, from 1921 to July 2016, in order to cover the great phases - or waves - of feminist activism. From a statistical sample, 579 texts were selected, organized in three different moments: the first wave (1921-1959), the second wave (1960-1989) and the third wave (1990 - 2016). Also, we interviewed 12 women linked to various faces and generations of Brazilian feminism, such as blacks, lesbians, trans, activists 2.0, feminist non-governmental organizations, among others. This research joins the tradition of feminist media studies, which have been concerned with journalistic coverage of women in the political system and civil society.